Extraction of series resistance and mobility degradation parameter in MOSFETs using iterative method - Noureddine Maouhoub; Khalid Rais (Computer Science and Information Technologies, 2020)
Series resistance and mobility attenuation parameter are parasitic phenomena that limit the scaling of advanced MOSFETs. In this work, an iterative method is proposed to extract the series resistance and mobility degradation parameter in short channel MOSFETs. It also allows us to extract the surface roughness amplitude. The principle of this method is based on the exponential model of effective mobility and the least squares methods. From these, two analytical equations are obtained to determine the series resistance and the low field mobility as function of the mobility degradation. The mobility attenuation parameter is extracted using an iterative procedure to minimize the root means squared error (RMSE) value. The results obtained by this technique for a single short channel device have shown the good agreement with measurements data at strong inversion.